Analysis of Journalism and Communication Studies in Europe's Top Ranked Universities: Competencies, Aims and Courses - Cervi, Laura; Simelio, Núria; Tejedor Calvo, Santiago (Journalism practice, 2021)
This article presents the results of a descriptive study that analyzes 17 curricula in Communication and Journalism of the 8 best ranked universities in Europe in the field of Communication, according to the QS World University Rankings. The research, using both quantitative and qualitative methodology, analyzes the academic curricula focusing on 687 courses, studying the type of courses, credit and subjects and their distribution in the curriculum. Good practices are identified, and trends are indicated in the design of the curricula. Moreover, a content analysis of the curricula of the selected Degrees has been carried out, based on a series of indicators: structure and credit system, objectives of the studies, competencies and professional profiles. The study shows that Journalism and Communication Degrees of the best ranked universities in Europe tend to focus mainly on theoretical courses, research methodologies and optional courses, and to encourage a critical look rather than focusing on an education model based on the professionalization and in the learning of tools and technologies. We conclude that the educational programs of the analyzed universities are not ready to adapt to the important structural changes that communication and the profession have undergone in recent years.